Levels of Adherence of an Exercise Referral Scheme in Primary Health Care: Effects on Clinical and Anthropometric Variables and Depressive Symptoms of Hypertensive Patients - Gallegos-Carrillo, Katia; Garcia-Peña, Carmen; Salgado-de-Snyder, Nelly; Salmerón, Jorge; Lobelo, Felipe (Frontiers in Physiology, 2021)
Among the modifiable health behaviors, the physical activity (PA) promotion has been one of the challenges in primary care, particularly how to translate the results of proven interventions and implement them in the real world. This study was aimed to compared if two programs designed for hypertensive patients achieve changes on clinical and anthropometrics variables, quality of life and depressive symptoms; and if higher levels of adherence of one of the interventions using an exercise referral (ER) approach achieve better health outcomes. Pragmatic cluster randomized trial, in 4 Primary Health Care Units (PHCUs). Physicians in PHCUs, identified hypertensive patients and assessed that they were eligible to be part on this trial. Each center was randomized to a brief PA counseling (BC, n=2) or an exercise referral (ER, n=2) intervention to conducted PA programs among hypertensive patients aged 35-70 years, self-reported as physically inactive. Outcome variables included changes in blood pressure levels, triglycerides, HDL cholesterol, fasting glucose, body mass index, rate waist/hip, abdominal obesity, and metabolic syndrome risk score, health-related quality of life and depressive symptoms. Longitudinal multilevel analyses assessed the effects of the BC and ER programs and the level of adherence of the ER on clinical, anthropometric and mental health variables, models were linear for continuous variables, and logistic for dichotomous variables. Differences were observed in triglycerides, BMI, metabolic risk scores variables and depressive symptoms among ER and BC programs. In addition, differences in the ER group were observed according to level of adherence in blood pressure levels, waist circumference and rate waist/hip, depressive symptoms and the mental health component of health-related quality of life. An ER program in comparison to a BC intervention is promoting changes in some specific health indicators of hypertensive patients, showing usefulness of this PA programs in primary health care facilities.